Developing Reading Assessment Instrument Using Digital Technology for Students with Dyslexia - Irdamurni Irdamurni; Johandri Taufan; Ardisal Ardisal (Journal of ICSAR, 2022)
This research aims to develop a reading assessment instrument using digital technology for students with dyslexia. The development functions are to (1) develop a reading assessment instrument based on digital technology for students with dyslexia, (2) examine the appropriateness of reading assessment instrument using Articulate Storyline to screen students with dyslexia. The data was collected through observation, interviews, and questionnaires. The data was validated by the material expert, information technology expert, and language expert in elementary school. The responses were also collected from teachers and students in inclusive elementary school as the users. A validation test was performed to find out the appropriateness of the developed assessment instrument. During the validation test, the experts assessed three aspects (content, digital technology, and language) and the teachers and students also gave their responses as the users of the assessment instrument. The total score of the validation results in all categories was 778 with an average score of 155.6. The aspect of content scored 3.79, the aspect of technology scored 3.60, and the aspect of language scored 3.85, with an average score of 11.24. Thus, the validation results by experts were categorized as very good and the final product that has been developed can be used as reading assessment instrument to screen students with dyslexia.